18 Relationship of myocardial strain and markers of myocardial injury to predict segmental recovery following acute st-segment elevation myocardial infarction. (26th April 2015) - Khan, JN; Greenwood, JP; Nazir, SA; Singh, A; Peebles, C; Wong, J; Gershlick, AH; McCann, GP
Abstract : Background: Late Gadolinium Enhancement (LGE) predicts functional recovery in stunned myocardium. Acutely post STEMI, LGE overestimates infarct and underestimates potential for functional recovery. There are no large studies comparing CMR predictors of segmental recovery in acute STEMI. Purpose: Determine whether segmental circumferential strain (Ecc), myocardial salvage (MSI), microvascular obstruction (MVO) and intramyocardial haemorrhage (IMH) predict segmental functional recovery and offer incremental predictive value to segmental extent of enhancement (SEE) acutely post-PPCI. Methods: 1.5T CMR was performed in 164 patients (2624 segments) at 48 hr and 9 month post-STEMI. LV function was assessed on wall-motion scoring on SSFP cines. Segmental dysfunction was WMS ≥2, improvement was WMS decrease of ≥1 and normalisation where WMS returned to 1 at follow-up. SEE and MVO were assessed on LGE using full-width half-maximum thresholding. Oedema and IMH were assessed on T2w imaging using Otsu's Automated Method. Ecc was Feature Tracking-derived. MSI was the proportion of non-infarcted segmental oedema. Accuracy of baseline SEE, segmental Ecc, MSI, MVO and IMH in predicting improvement and normalisation in dysfunctional segments was assessed with Receiver Operator Curves. Results: 32% of segments were dysfunctional at baseline and 19% at follow-up. With increasing SEE, segmental function worsened and proportion of dysfunctional segments recovering decreased. However 33% of SEE >75% segments improved (Figure 1a ). SEE was a strong predictor of improvement (AUC 0.708) and normalisation (AUC 0.807). SEE was a stronger predictor than MVO, IMH and Ecc (p < 0.01 for all). MVO, IMH and Ecc were weak predictors. Combining SEE with MVO, IMH, Ecc or MSI did not improve predictive accuracy versus SEE alone (Figure 1b –1c ). Conclusions: This is the largest study assessing CMR predictors of segmental recovery in acute STEMI. Baseline SEE was the strongest predictor. Ecc, MSI, MVO and IMH provided no incremental predictive value to SEE. Functional improvement can occur where SEE >75%.